Stimulation-Induced Side Effects of Deep Brain Stimulation in the Ventralis Intermedius and Posterior Subthalamic Area for Essential Tremor - Myung Ji Kim; Kyung Won Chang; So Hee Park; Won Seok Chang; Hyun Ho Jung; Jin Woo Chang (Frontiers in Neurology, 2021)
Deep brain stimulation (DBS) targeting the ventralis intermedius (VIM) nucleus of the thalamus and the posterior subthalamic area (PSA) has been shown to be an effective treatment for essential tremor (ET). The aim of this study was to compare the stimulation-induced side effects of DBS targeting the VIM and PSA using a single electrode. Patients with medication-refractory ET who underwent DBS electrode implantation between July 2011 and October 2020 using a surgical technique that simultaneously targets the VIM and PSA with a single electrode were enrolled in this study. A total of 93 patients with ET who had 115 implanted DBS electrodes (71 unilateral and 22 bilateral) were enrolled. The Clinical Rating Scale for Tremor (CRST) subscores improved from 20.0 preoperatively to 4.3 (78.5% reduction) at 6 months, 6.3 (68.5% reduction) at 1 year, and 6.5 (67.5% reduction) at 2 years postoperation. The best clinical effect was achieved in the PSA at significantly lower stimulation amplitudes. Gait disturbance and clumsiness in the leg was found in 13 patients (14.0%) upon stimulation of the PSA and in significantly few patients upon stimulation of the VIM (p = 0.0002). Fourteen patients (15.1%) experienced dysarthria when the VIM was stimulated; this number was significantly more than that with PSA stimulation (p = 0.0233). Transient paresthesia occurred in 13 patients (14.0%) after PSA stimulation and in six patients (6.5%) after VIM stimulation. Gait disturbance and dysarthria were significantly more prevalent in patients undergoing bilateral DBS than in those undergoing unilateral DBS (p = 0.00112 and p = 0.0011, respectively). Paresthesia resolved either after reducing the amplitude or switching to bipolar stimulation. However, to control gait disturbance and dysarthria, some loss of optimal tremor control was necessary at that particular electrode contact. In the present study, the most common stimulation-induced side effect associated with VIM DBS was dysarthria, while that associated with PSA DBS was gait disturbance. Significantly, more side effects were associated with bilateral DBS than with unilateral DBS. Therefore, changing active DBS contacts to simultaneous targeting of the VIM and PSA may be especially helpful for ameliorating stimulation-induced side effects.